Quantitative Characteristics of the Okra [Abelmoschus esculentus (L.) Moench] Root System Under Water Constraints - Nana, Rasmata; Badiel, Badoua; Ouedraogo, Hamed Mahamadi; Soubande, Frederic; Tamini, Zoumbiesse (European Scientific Journal, ESJ, 2019)
The depth and density of roots play a determining role in the maintenance of the water supply of the plant in a condition of water deficit in the soil. Under water deficit conditions, a root system developing deep in the soil is the most desired character. This study aims to determine adaptive performance of the okra root system under water stress. Thus, the effects of water deficit induced by restriction of soil field capacity (SFC) to 60%, 40% and 20% were studied in two varieties of okra (V1 and V2) and compared to a control water regime ( 100% SFC irrigation). Results showed that the number of primary roots, the root volume, the root dry matter, the length of the main root and the root fineness varied according to varieties, water regimes and their interaction. However, varietal differences were observed for the characters length of the main root and root fineness. In addition, a significant difference and very highly significant were respectively observed for the interaction * variety hydric regime on the number of primary roots(p = 0.016) and the length of the main root (p ≤ 0.001). Under water regimes at 60% SFC, 40% SFC or 20% SFC, there is an increase in length of the main root of the varietyV2; but for the variety V1, the increase was noted in the plants irrigated at 40% SFC. On the other hand, in both varieties, root fineness increased under all restrictive water regimes.